A feminist political ecology of agricultural mechanization and evolving gendered on-farm labor dynamics in northern Ghana. (2nd September 2019) - Kansanga, Moses Mosonsieyiri; Antabe, Roger; Sano, Yujiro; Mason-Renton, Sarah; Luginaah, Isaac
Abstract: Although agricultural mechanization is central to the renewed agenda for achieving an African Green Revolution, the increased deployment of mechanized technologies has been without critical analysis of the impacts on traditional agrarian labor division practices. Drawing on the experiences of smallholder farmers ( n  = 60) in northern Ghana using in-depth interviews, we examined the gendered labor implications of agricultural mechanization and how women and men may be responding to evolving on-farm labor dynamics. Our findings reveal a skewed deployment of mechanized technologies in favor of the culturally ascribed on-farm roles of men. This situation has produced a disproportionate labor burden on rural women who are compelled to endure manually in their non-mechanized culturally ascribed roles of sowing and harvesting even as farms are expanding. Although, generally, rural women bear the brunt of these incipient labor demands, certain intersecting vulnerabilities such as belonging to a monogamous household and having fewer or no female children tend to worsen the plight of some women. While gendered labor substitution could balance the disproportionate workload on women, the prevalence of strict culturally constructed gendered labor norms forestalls this potential. Given the painful routine choices rural women make to balance household labor demands, we highlight the need for gender-sensitive mechanization models and policy approaches that address prevailing social inequalities.